Stuck in the Smoke: When Carbon Meets Capital in the Global South - Luthfi Hasanal Bolqiah; Fullah Jumaynah (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
Over the past decade, carbon taxation has emerged as a central instrument in global emission reduction efforts. Yet in many developing countries of the Global South, its implementation has fallen short of the urgency posed by the climate crisis. A significant gap in the literature remains: how industrial resistance and domestic power configurations shape the design and enactment of carbon tax policies. This study examines the dynamics of industrial resistance to carbon taxation in four Global South countries—India, South Africa, Mexico, and South Korea—by highlighting the strategic alliances forged between the state and carbon-intensive industries. This study adopts a qualitative approach, employing a comparative research design to analyze policy documents, statistical data from the World Bank, IEA, and Carbon Pricing Dashboard, along with relevant academic literature. Findings indicate that in all four cases, the state tends not to act as a transformative agent, but rather as a facilitator of fiscal and political compromises with industrial actors. The resulting policies are largely symbolic—characterized by low tax rates, broad exemptions, and the absence of escalation strategies. Framed through the lens of strategic state–capital alliances, this study argues that state–market relations in the Global South cannot be understood purely in technocratic terms, but must be seen as configurations of power that shape the trajectory of energy transitions. These findings offer important theoretical implications for climate policy research and the political economy of development.